Characterization, immunostimulatory and antitumor activities of a β-galactoglucofurannan from cultivated Sanghuangporus vaninii under forest - Cheng, Junwen; Wang, Yanbin; Song, Jiling; Liu, Yu; Ji, Weiwei; He, Liang; Wei, Hailong; Hu, Chuanjiu; Jiang, Yihan; Xing, Yiqi; Huang, Xubo; Ding, Hongmei; et al. (Frontiers in Nutrition, 2022)
A biomacromolecule, named as β-galactoglucofurannan (SVPS2), was isolated from the cultivated parts of Sanghuangporus vaninii under the forest. Its advanced structure was analyzed by a series of techniques including GC-MS, methylation, NMR, MALS as well as AFM. The results indicated that SVPS2 was a kind of 1, 5-linked β-Glucofurannan consisting of β-glucose, β-galactose and α-fucose with 23.4 KDa. It exhibited a single-stranded chain with an average height of 0.65 nm in saline solution. SVPS2 could mediate the apoptosis of HT-29 cells. Western blot assay revealed an upregulation of Bax, Cytochrome c, cleaved caspase-3, Fas, Fas-L and FADD by SVPS2, accompanied by a downregulation of Bcl-2. These results collectively demonstrate that antitumor mechanism of SVPS2 may be associated with enhancing immune response and inducing apoptosis of tumor cells in vitro. Therefore, SVPS2 might be utilized as a promising therapeutic agent against colon cancer and functional food with immunomodulatory activity.